P608 Time to onset of effect of biologics and small molecules in moderate-to-severe or acute severe ulcerative colitis – a systematic review and network meta-analysis. (30th January 2023) - Attauabi, M; Dahl, E K; Burisch, J; Gubatan, J; Nielsen, O H; Seidelin, J B
Abstract: Background: Time to response of advanced therapies is an important parameter due to the symptom load and risk of disease complications in moderate-to-severe ulcerative colitis (UC), but comparative data are lacking. We aimed to assess the comparative onset of effectiveness of biological therapies and small molecules for this patient population. Methods: In this systematic review and network meta-analysis, we searched MEDLINE, Embase, and Cochrane Central Register of Controlled Trials from inception to 24 August 2022, for randomized controlled trials or open-label studies assessing the effectiveness of biologics or small molecule drugs within the first six weeks of treatment in adults with UC. The co-primary outcomes were the induction of clinical response and clinical remission at week 2. Network meta-analyses was conducted under the Bayesian framework. This study is registered with PROSPERO: CRD42021250236. Results: The systematic literature search identified 20, 406 citations, of which 28 studies comprising 11, 155 patients fulfilled the eligibility criteria (Figure 1). All agents were superior to placebo for the induction of a clinical response at week 2 (Figure 2). Upadacitinib ranked highest for induction of clinical response and clinical remission at week 2 and was significantly superior to all agents but tofacitinib, which ranked second highest (Figures 3-4). Although the rankings remained consistent, no differences between upadacitinib and biological therapies were demonstrated in the sensitivity analyses of partial Mayo clinic score response or resolution of rectal bleeding at week 2. Tumor necrosis factor-α (TNF) inhibitors were significantly superior to vedolizumab and ustekinumab for patient-reported outcome-2 (PRO-2) remission at week 2 in bio-naïve patients. Ustekinumab, and ozanimod ranked lowest across all endpoints. Figure 1: Flow diagram of assessment of studies identified in the systematic review Figure 2: Forest plot for achievement of clinical response at week 2 among patients with moderate to severe ulcerative colitis Figure 3: Indirect comparison of biologics and small molecule drugs for the induction of clinical response at week 2 in patients with moderate-to-severe ulcerative colitis Figure 4: Indirect comparison of biologics and small molecule drugs for the induction of clinical remission at week 2 in patients with moderate-to-severe ulcerative colitis Conclusion: In this network meta-analysis, we found upadacitinib to be significantly superior to all agents but tofacitinib for induction of clinical response and clinical remission two weeks after treatment initiation. In contrast, ustekinumab and ozanimod ranked lowest. Our findings help to establish the evidence regarding the onset of effectiveness of advanced therapies.